Implementation of Frugal Living to Lead to A Prosperous Quality of Life in Personal Financial Planning Literature Study - Ahmad Tojiri (Publikasi Indonesia, 2026)
Amid global economic uncertainty and increasing consumptive lifestyles, many individuals face challenges in achieving a prosperous quality of life through personal financial planning. Frugal living practices are emerging as a promising strategy to overcome these challenges. This research aims to comprehensively investigate the practice of frugal living as a strategy towards improving the quality of a prosperous life in the context of personal financial planning, through a literature review approach. With the rise of discourse on sustainability and consumption awareness, this study examines a wide range of relevant scientific literature to understand the concept of frugal living, its principles, and its implications for individual financial well-being. The research method used was thematic analysis of the publication of journals, books, and research reports published in a certain time frame. The study's main results show that frugal living is not just about extreme saving, but rather a value-first mindset, prioritization, and waste reduction, which significantly contributes to the achievement of long-term financial goals, reduced financial stress, and increased life satisfaction. The consistent application of frugal living allows individuals to allocate resources more wisely, save more, invest smartly, and ultimately achieve sustainable prosperity. The conclusion of this study confirms that frugal living is an important instrument in personal financial planning to achieve a prosperous quality of life in the modern era.